Numerical Simulation of an Industrial Absorber for Dehydration of Natural Gas Using Triethylene Glycol - Kenneth Kekpugile Dagde; Jackson Gunorubon Akpa (Journal of Engineering)
Models of an absorber for dehydration of natural gas using triethylene glycol are presented. The models were developed by applying the law of conservation of mass and energy to predict the variation of water content of gas and the temperature of the gas and liquid with time along the packing height. The models were integrated numerically using the finite divided difference scheme and incorporated into the MATLAB code. The results obtained agreed reasonably well with industrial plant data obtained from an SPDC TEG unit in Niger-Delta, Nigeria. Model prediction showed a percentage deviation of 8.65% for gas water content and 3.41% and 9.18% for exit temperature of gas and liquid, respectively.